Fizisko aktivitāšu veicinoša vide pirmsskolas izglītības iestādē 4 – 5 gadu veciem bērniem - Radziņa, Ilvija (Latvijas Universitāte, 2021)
Apzināt, kā mainās bērnu aktivitāte pirmsskolas izglītības iestādē fiziskajās aktivitātēs, mainoties videi. Darbā sākotnēji tiek analizēti literatūras avoti un pēc tam izvirzīti kritēriji, pēc kuriem tiek veidota fizisko aktivitāšu telpas kritēriji. Tiek pētīts kāda vide veicina bērnu aktivitāti piedalīties un veikt fiziskās aktivitātes. Darbā tiek veikti bērnu novērojumi veicot fiziskās aktivitātes pirmsskolas izglītības iestādes ''X'' telpās un Ogres novada sporta centra telpās.

Scientific work is based on the environment of pysical activity in pre-school and what this environment should be like. Physical activity is one of the most important thing for maintaining a childrens health. the qualification work is based on the physical activities of 4-5 year old children in pre-school. From the start author of the work are analyzing the literature source. And after that criteria are made for physical activity space and filled in table. In the work, childrens observations are made both in pre-school education space and sports hall. The queastion of the qualification work is - how do childrens activity and participation in physical activities in pre-school aducational institution change as the physical environment changes?
Physicalactivity-promoting enviroment in a pre-school educational institution for 4 – 5 years old children
Keywords: Pedagoģija; Fiziskās aktivitātes; pirmsskolas izglītības iestāde; veicinoša vide; 4-5gadus veci bērni; physical activities